Autologous Surgical Reconstruction for True Venous Hemodialysis access Aneurysms–-Techniques and Results. Issue 5 (September 2014) - Sigala, Fragiska; Kontis, Elissaios; Saßen, Regine; Mickley, Volker
Purpose: Due to their relatively low complication rates autogenous arteriovenous fistulas (AVFs) are the preferred access for hemodialysis. In long-standing AVF, however, aneurysmatic degeneration of the fistula vein can develop. Several treatment options have been published. We evaluated our experience with autologous surgical reconstruction in patients with AVF aneurysms in order to assess complication and patency rates. Methods: Demographics and comorbidities of all patients operated on for true AVF aneurysms in our institution, during a 7-year period, were reviewed. Access function and surgical outcomes were evaluated with pre- and postoperative Doppler ultrasonography. Patient survival, primary and secondary access patency rates are presented. Results: From April 2006 through March 2013, 31 patients presented with access-associated upper extremity venous aneurysms. The mean time from AVF creation to aneurysm formation was 4.9±3.6 years. The most frequent indication for surgery was aneurysm-associated stenosis (n=16) followed by high flow (n=9), complete thrombosis (n=3) and uncontrolled bleeding (n=3). All patients had autologous reconstructions: 5 resections with end-to-end anastomosis and 26 aneurysmorrhaphies. Overall patient survival at 1 and 2 years was 89% and 84%, respectively. The primary (secondary) patency rates at 6 mo, 1 and 2 years were 87%, 81% and 81% (96%, 96% and 90%), respectively. Conclusions: Autologous surgical reconstruction is feasible in the majority of AVF aneurysms. It preserves fistula function and–-in contrast to graft interposition and endovascular repair–-keeps the advantages of an autogenous access: low complication and high patency rates.